Intelkam’s Efforts to Prevent Conflict Between Silat Schools at Ngawi Police - Sebastian, Adriel Timothy (Advances in Police Science Research Journal, 2024)
The researcher raised the final project with the problem "Raising Efforts in Preventing Conflicts Between The Pencak Silat College at the Ngawi Police Station". The purpose of this study is to determine the implementation of intelligence raising in preventing conflicts between The Pencak Silat College at the Ngawi Police Station and the factors that influence intelligence raising efforts in preventing conflicts between The Pencak Silat College at the Ngawi Police Station.Qualitative research is used in this study and Field Research as the type of research. Interviews, interviews, observations, and document studies are carried out by the author to meet the required data. Apart from these three things, the author also uses various references such as articles, books, journals, and electronic media news related to the variables discussed to obtain data.To fulfill the objectives of the study, researchers use management theory and SWOT theory. In addition to using theory, researchers also use the concept of intelligence gathering and the concept of effort. The concept of intelligence raising is based on Perkabaintelkam Number 1 of 2023 annex 3 (three) concerning beheading.Raising efforts are a form of activity carried out by the Intelkam Unit to create ideal kamtibmas conditions. However, in its implementation, the raising efforts carried out by the intelligence unit are still considered unsuccessful in preventing 2 conflicts between The Pencak Silat College in the jurisdiction of the Ngawi Regional Police.The results in this study show that there are still shortcomings in the raising efforts carried out by the Ngawi Police intelligence unit, therefore the improvement of intelligence raising efforts must be carried out as a form of effort to prevent conflicts between The Pencak Silat College in the jurisdiction of the Ngawi Police Station.